2004
DOI: 10.1158/0008-5472.can-03-3852
|View full text |Cite
|
Sign up to set email alerts
|

Association of Breast Cancer DNA Methylation Profiles with Hormone Receptor Status and Response to Tamoxifen

Abstract: We have generated DNA methylation profiles of 148 human breast tumors and found significant differences in hormone receptor (HR) status between clusters of DNA methylation profiles. Of 35 DNA methylation markers analyzed, the ESR1 gene, encoding estrogen receptor ␣, proved to be the best predictor of progesterone receptor status, whereas methylation of the PGR gene, encoding progesterone receptor, was the best predictor of estrogen receptor status. ESR1 methylation outperformed HR status as a predictor of clin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
280
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(300 citation statements)
references
References 35 publications
16
280
4
Order By: Relevance
“…Previous studies have reported the association of DNA methylation patterns with molecular subtypes of breast cancer through hormone receptor and HER2/neu status. [14][15][16][17]35 In an early study by Sunami et al, 14 double-negative (ER-negative, HER2/neunegative) breast cancers, corresponding to the basal-like subtype, were reported to have lower frequencies of RASSF1A, GSTP1, and APC methylation, and this was confirmed in the present study. Suijkerbuijk et al 36 examined the methylation of 11 genes involved in breast carcinogenesis (RARB, RASSF1, TWIST, CCND2, ESR1, SCGB3A1, BRCA1, BRCA2, CDKN2A, APC, CDH1) by quantitative multiplex methylation-specific PCR in BRAC1-associated and sporadic breast cancers, and showed that the median values for RASSF1, TWIST, SCGB3A1, APC, and the cumulative methylation index for the 11 genes, were significantly lower in BRAC1-associated hereditary breast cancers than in sporadic ones.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have reported the association of DNA methylation patterns with molecular subtypes of breast cancer through hormone receptor and HER2/neu status. [14][15][16][17]35 In an early study by Sunami et al, 14 double-negative (ER-negative, HER2/neunegative) breast cancers, corresponding to the basal-like subtype, were reported to have lower frequencies of RASSF1A, GSTP1, and APC methylation, and this was confirmed in the present study. Suijkerbuijk et al 36 examined the methylation of 11 genes involved in breast carcinogenesis (RARB, RASSF1, TWIST, CCND2, ESR1, SCGB3A1, BRCA1, BRCA2, CDKN2A, APC, CDH1) by quantitative multiplex methylation-specific PCR in BRAC1-associated and sporadic breast cancers, and showed that the median values for RASSF1, TWIST, SCGB3A1, APC, and the cumulative methylation index for the 11 genes, were significantly lower in BRAC1-associated hereditary breast cancers than in sporadic ones.…”
Section: Discussionsupporting
confidence: 85%
“…7 There are reports that promoter CpG island hypermethylation is associated with various histopathologic characteristics of breast cancers, including histologic type, 10,11 tumor grade, 12,13 hormone receptor, and HER2/neu status. [14][15][16][17] Array-based comprehensive DNA methylation profiling has shown that breast cancer molecular subtypes have their own methylation profiles. [18][19][20][21] Moreover, these different methylation profiles were evident throughout the CpG islands of the genome, not limited to functional genes.…”
mentioning
confidence: 99%
“…DIRAS3 is often imprinted and LOH in breast and ovarian tumors most often affect the non-imprinted allele [30]. Furthermore, methylation of the DIRAS3 promoter has been demonstrated to predict poor survival in breast cancer [31]. This illustrates that different mechanisms, in this case allelic loss and methylation, can deactivate the same gene and support the viability of our method to detect these genes.…”
Section: Candidate Genesmentioning
confidence: 53%
“…13 All primers and probes have been published elsewhere. 21 The differences in amounts of input genomic DNA were normalized by the collagen type II, alpha 1 gene (COL2A1). The percentage of methylated reference was calculated as follows: the methylated MGMT/COL2A1 ratio for each sample was divided by the same ratio obtained for a SssItreated genomic DNA used as standard, and values were multiplied by 100.…”
Section: Methylightmentioning
confidence: 99%